(untitled) (Research, Society and Development, 2022)
The present study aims to describe Kaposi’s Sarcoma disease as a condition related to patients with HIV/AIDS and its characteristics. Furthermore, the study sought to report the main clinical manifestations of the disease, thus seeking a quick and effective diagnosis, aiming at treatment for patients affected by the disease. The chosen methodology was a bibliographic review of the integrative literature review type. To carry out this study, the following databases were consulted: MEDLINE, Scholar Google, LILACS, SCIELO and Repositories. The Descriptors in Health Sciences (DeCS) were used in an associated way: Kaposi’s Sarcoma, Human Immunodeficiency Virus, AIDS, Symptoms and Treatment. Initially, 205 studies with the proposed theme; among these, 105 studies were excluded, according to the established exclusion criteria. After applying the inclusion criteria, 12 studies remained. Kaposi’s Sarcoma is a rare neoplasm that a few years ago was hardly seen by the medical community. However, with the increase in HIV infection in populations at higher risk of developing this neoplasm and with the numerous late diagnoses of HIV infection, it has been gaining ground in the health system.